Gambus Al-Mubarok’s Studio: Form and Structure of Music - Hanifah, Hanifah Suaidi; Sumaryanto. F, Totok; Wadiyo, Wadiyo (Catharsis, 2019)
The music of Gambus is a musical that has Middle East style and identic with Islamic nuances, from song lyrics, dances to musical instruments that are used rhythmically, as well as melodic songs with unique characteristics possessed by stringed instrument, namely Gambus. This study aimed to analyze the form and structure of Gambus music in the Al-Mubarok studio at Palembang city. The method used a qualitative research case study design. The research data were collected through observation, interview, and documentation techniques and also using triangulation techniques in testing the credibility of the data. In the process of analyzing data, the data validation technique was carried out through several stages, namely reduction, presentation of data, and drawing conclusions. The results of this study were to provide knowledge and become a reference for Gambus music consisting of two elements of time and melody. Meanwhile, the structure of Gambus music had repeated sentences and periods. The researcher hopes this research can be useful for the public and readers who want to know the oldest Gambus music studio in Palembang city that still maintains the authenticity of their ancestor’s art in Sriwijaya.